SEJARAH PERKEMBANGAN PONDOK PESANTREN DAARUN NAHDHAH THAWALIB BANGKINANG KABUPATEN KAMPAR TAHUN 1948-2019 - Rezha, Dhea Alvionita; Isjoni, Isjoni; Asril, Asril (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract:Daarun Nahdhah is the oldest Islamic boarding school in Kampar Regency, which gives birth to many skilled alumni according to their respective fields. Daarun Nahdhah Thawalib Bangkinang Islamic Boarding School is a continuation of the Daarul Mu'alimin Madrasah led by H. Syeh Abdul Malik. Daarul Mu'alimin was founded in 1923. About six years of activity the Daarul Mu'alimin Madrasa was stopped, the late K.H. Muhammad Nurmahyuddin, a student of Syeh Abdul Malik, revived the hut with the name Daarun Nahdhah Thawalib Bangkinang. The purpose of this study is to find out the history of development, the education system, the driving factors as well as the inhibiting factors in the development and contribution of the founding family and alumni to the development of the Daarun Nahdhah Islamic Boarding School. The method used is the historical method where data is collected through observation, interviews, documentation, and literature study. Data analysis uses historical writing method which consists of several stages, namely heuristics, verification, interpretation, and historiography. Research time starts fromthe submission of the proposal title until the completion of the thesis of the author. The results showed that the Daarun Nahdhah Islamic Boarding School had developed very rapidly from its inception until now. These developments include improvements in facilities and infrastructure, teachers, students, and curriculum. This is inseparable from the efforts made by Daarun Nahdhah Islamic Boarding School in improving quality and quantity in Kampar Distric.KeyWords:History, Development, Daarun Nahdhah Islamic Boarding School, Kampar Regency